Bio-hydrocarbon Production from Sorbitol using FeI2 to accelerate HI regeneration reaction. Issue 1 (April 2020) - Krisnayana, Rina; Subagjo,; Rasrendra, CB; Hernas Soerawidjaja, Tatang
Abstract: Petroleum reserve decrease, while the dominant fuel used for daily needs and industry comes from petroleum. These fossil fuels cause global warming. Because of the above, hydrocarbon fuel from biomass is needed. On the laboratory-scale (1990's), bio-hydrocarbon can be produced from sorbitol. This was obtained in 2 steps. The first step uses HI and H3 PO3 and the second step is heating using KOH-ethanol. In the first step, HI regeneration using H3 PO3 produces H3 PO4, which is difficult to be reduced back to H3 PO3 . It makes the process become expensive, so it needs modification. The modification is done by using HCOOH for regenerating iodine into HI. In order to reduce the need for HI in the system, HI regeneration reaction is expected not slower than sorbitol reduction reaction by HI, so it requires FeI2 catalyst. Referring to the previous description, the purpose of this study is to investigate bio-hydrocarbon production from sorbitol using HI for sorbitol conversion, HCOOH for iodine regeneration, and FeI2 as catalyst to accelerate HI regeneration reaction. A sorbitol, HI, HCOOH and FeI2 mixture is refluxed in three-neck flask. Bio-hydrocarbon (C6 H12 ) can be produced from sorbitol. Maximum sorbitol conversion is 85.84%, maximum iodohexane yield is 62.41% and maximum biohydrocarbon (C6 H12 ) yield is 64.2%.